Temperamen dan Kerentanan Adiksi Smartphone pada Mahasiswa Keperawatan - Muhamad Nurmansyah; Dina Mariana Larira; Musfira Ahmad (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The percentage of internet usage and smartphone ownership has increased rapidly in the last two years. The high percentage of smartphone ownership raises questions about the dangers of their use. The increasingly reported use of smartphones results in an increased prevalence of sleep disorders, depression and anxiety. In more severe conditions, smartphone use can lead to addiction. In preventing these impacts, of course, in the early stages it is necessary to carry out early detection of disturbances. Early detection should be done by considering individual risk factors, one of which is temperament personality type. The purpose of this study was to determine the relationship between temperament and vulnerability to smartphone addiction in nursing students. This study applied a cross-sectional design. Respondents were 188 nursing students at Sam Ratulangi University. Data was collected by filling out questionnaires and then analyzed by Chi-square test. The results of the analysis for the relationship between novelty seeking temperament and smartphone addiction was p = 0.014, OR = 2.08, r = 0.180, the relationship between reward dependence temperament and smartphone addiction was p = 0.029, OR = 1.93.08, r = 0.159, while the relationship between harm avoidance temperament and smartphone addiction was p = 0.408. It was concluded that smartphone addiction is related to novelty seeking and reward dependence temperament.Keywords: temperament; smartphone addiction; vulnerability: nursing students ABSTRAK Persentase penggunaan internet dan kepemilikan smartphone meningkat dengan pesat dalam dua tahun terakhir. Tingginya persentase kepemilikan smartphone menimbulkan pertanyaan tentang bahaya penggunaannya. Penggunaan smartphone yang semakin sering dilaporkan mengakibatkan peningkatan prevalensi gangguan tidur, depresi dan kecemasan. Pada kondisi yang lebih berat, penggunaan smartphone dapat menimbulkan adiksi. Dalam pencegahan dampak tersebut, tentunya tahapan awal perlu dilakukan deteksi dini gangguan. Deteksi dini sebaiknya dilakukan dengan mempertimbangkan faktor resiko individu, salah satunya yaitu tipe kepribadian temperamen. Tujuan penelitian ini untuk mengetahui hubungan antara temperamen dengan kerentanan adiksi smartphone pada mahasiswa keperawatan. Penelitian ini menerapkan desain cross-sectional. Responden adalah 188 mahasiswa keperawatan Universitas Sam Ratulangi. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis dengan uji Chi-square. Hasil analisis untuk hubungan antara temperamen novelty seeking dengan adiksi smartphone adalah p = 0,014, OR = 2,08, r = 0,180, hubungan antara temperamen reward dependence dengan adiksi smartphone adalah p = 0,029, OR = 1,93,08, r = 0,159, sedangkan hubungan antara temperamen harm avoidance dengan adiksi smartphone adalah p = 0,408. Disimpulkan bahwa adiksi smartphone berhubungan dengan temperamen novelty seeking dan reward dependence.Kata kunci: temperamen; adiksi smartphone; kerentanan: mahasiswa keperawatan